Perbandingan Efektifitas Kombinasi Teknik Marmet Dan Pijat Oksitosin Dengan Breast Care Terhadap Produksi Asi Pada Ibu Post Partum - Ira Titisari; Rahajeng Siti Nur Rahmawati (coba, 2016)
Breast milk is the baby food of God's creation that can not be replaced with other foods and beverages. Breast milk is the best baby food and every baby is entitled to breastfeeding. Children exclusively breastfed 14 times more likely to survive in the first six months of life than children who are not breastfed. Start feeding on the first day after birth could reduce newborn mortality risk by 45 percent. Breastfeeding also supports a child's ability to learn and help prevent obesity and chronic diseases later in life. ASI Marmet Technique is issued manually and help milk ejection reflex (Milk Ejection Reflex) has worked for thousands of women in ways not previously owned. Oxytocin massage is massage on the neck, back and along the spine (vertebrae) bone costae until the fifth to sixth. Massage can stimulate the release of oxytocin hormone oxytocin. Oxytocin reflex works spur breast milk. Breast care is the maintenance of the breast is done to facilitate breastfeeding and avoiding difficulties during breastfeeding by doing massage (Welford, 2009). The purpose of this study was to compare the effectiveness of massage techniques Marmet and oxytocin with breast care to the mother's milk production in the post partum. This type of quasi experimental research design The research design used Post Only Design, The population in this study were all post-partum mothers who met the inclusion criteria for the study RSIA Melinda Kediri. A sampling technique that consecutive sampling with a sample of 30 respondents. Data collection is done by dividing into 2 groups: group given Marmet and massage techniques oxytocin and the group given breast care, and to assess milk production using observation sheet milk production. Data analysis technique used was Wilcoxon Mann Whitney U Test. The result showed a p-value arithmetic (0.870)> Alpa = (0.05), which means there is no difference in the combined administration of Marmet and massage techniques and breast care oxytocin on milk production. The conclusion from this study is there is no difference in milk production in mothers postpartum conducted Marmet technique and massage oxytocin with post partum mothers who do breast care. The researchers suggest is that all medical personnel can continue to support the improvement of the quality of obstetric care with attention to maternal postpartum milk production which could have an impact on the process of breastfeeding. Keywords : Marmet Technique, massage oxytocin, breast care, breast milk production, post partum